2020
DOI: 10.1016/j.jcv.2020.104529
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of commercial lateral flow immunoassays and ELISA for SARS-CoV-2 antibody detection

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 13 publications
(24 reference statements)
6
74
1
Order By: Relevance
“…Our data indicate that living with diagnosed or symptomatic people was more relevant in domestic environment than in the workplace, which can be justified by more intimate contact and extensive sharing of areas, in spite the guidelines advising family members to distance themselves. is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint The copyright holder for this this version posted October 21, 2020. ; https://doi.org/10.1101/2020.10.19.20213421 doi: medRxiv preprint Professionals from laboratory areas were 25% while workers who had no direct contact with patients (administrative areas, security and cleaning staff) had a higher infection rate, especially in the areas of logistics (Faíco-Filho, et al, 2020) In our study, we chose to use a rapid test for preliminary results, despite the its reported performance (Sensitivity: 86, 43% [95% CI: 82, 51%~89, 58%] and Specificity: 99, 57% [95% CI: 97, 63%~99,92%]).. We chose to use the serum obtained from the peripheral blood because the test performance was better in terms of sensitivity when used in serum and not in blood capillary, as suggested in others studies (Santos et al, Wu et al, 2020;Serrano et al, 2020). This test may be performed with whole blood, plasma and serum.…”
Section: Correlation Between Seropositivity and Professional Activitymentioning
confidence: 99%
“…Our data indicate that living with diagnosed or symptomatic people was more relevant in domestic environment than in the workplace, which can be justified by more intimate contact and extensive sharing of areas, in spite the guidelines advising family members to distance themselves. is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint The copyright holder for this this version posted October 21, 2020. ; https://doi.org/10.1101/2020.10.19.20213421 doi: medRxiv preprint Professionals from laboratory areas were 25% while workers who had no direct contact with patients (administrative areas, security and cleaning staff) had a higher infection rate, especially in the areas of logistics (Faíco-Filho, et al, 2020) In our study, we chose to use a rapid test for preliminary results, despite the its reported performance (Sensitivity: 86, 43% [95% CI: 82, 51%~89, 58%] and Specificity: 99, 57% [95% CI: 97, 63%~99,92%]).. We chose to use the serum obtained from the peripheral blood because the test performance was better in terms of sensitivity when used in serum and not in blood capillary, as suggested in others studies (Santos et al, Wu et al, 2020;Serrano et al, 2020). This test may be performed with whole blood, plasma and serum.…”
Section: Correlation Between Seropositivity and Professional Activitymentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 4, 2020. ; https://doi.org/10.1101/2020.12.02.20242750 doi: medRxiv preprint including serum IgG ELISAs, albeit at higher cost [18]. These tools, however, could be useful for determining community level immunity, either due to infection itself or after vaccination, especially in areas where access to more sophisticated and expensive quantitative analysis may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish study compared the sensitivity and specificity of a commercial IgG and IgA ELISA (Euroimmun) with three lateral flow immunoassays (Hangzhou Alltest Biotech, Wuhan UNscience Biotechnology, and Guangzhou Wondfo Biotech) from 109 COVID-19 patients. 27 The Euroimmun SARS-CoV-2 test had a sensitivity and specificity of 100% and 80.6%, respectively. The sensitivities of the lateral flow immunoassays ranged from 81.2% to 100%; the specificities ranged from 80.6% to 100%.…”
Section: Spanish Antibody Studiesmentioning
confidence: 97%
“…The sensitivities of the lateral flow immunoassays ranged from 81.2% to 100%; the specificities ranged from 80.6% to 100%. 27 Physicians are encouraged to utilize lateral flow immunoassays with the highest sensitivity possible. A subsequent Spanish study evaluated a lateral flow immunoassay AllTest COVID-19 IgG/IgM using serum samples from 100 SARS-CoV-2-negative patients and 90 patients with SARS-CoV-2 confirmed with nasopharyngeal RT-PCR.…”
Section: Spanish Antibody Studiesmentioning
confidence: 99%